Survival of critically ill people with COVID-19 and acute kidney injury undergoing hemodialysis in public and private hospitals in Joinville: a cohort study, 2020-2021 - Elviani Basso Moura; Bruna de Albuquerque Catelano; Fernanda Perito de Aguiar; Helbert do Nascimento Lima; Paulo Henrique Condeixa de França (Epidemiologia e Serviços de Saúde)
Abstract Objective: To compare the 90-day survival of critically ill people with COVID-19 and acute kidney injury in intensive care units (ICU) of public and private hospitals. Methods: This was a retrospective cohort study of critically ill people with COVID-19 and acute kidney injury undergoing hemodialysis in Joinville, Santa Catarina state. Results: The 90-day survival rate in public ICU was 15.7% (95%CI 8.4; 25.1), while in private ICU it was 37.7% (95%CI 24.9; 50.5%). In the multivariate analysis adjusted for sociodemographic variables (Hazard ratio (HR) 2.01; 95%CI 1.31; 3.08) and comorbidities (HR 2.09; 95%CI 1.30; 3.37), admission to a public ICU was associated with a higher risk of death. After including severity of illness, admission to a public ICU was not associated with an increased risk of death compared to private ICU (HR 0.79; 95%CI 0.45; 1.42). Conclusion: Measures implemented during the COVID-19 pandemic may have reduced inequalities between health systems for critically ill patients with acute kidney injury.